Sepsis-Associated Encephalopathy: A Mini-Review of Inflammation in the Brain and Body - Ito, Hiroshi; Hosomi, Sanae; Koyama, Yoshihisa; Matsumoto, Hisatake; Imamura, Yukio; Ogura, Hiroshi; Oda, Jun (Frontiers in Aging Neuroscience, 2022)
Sepsis is defined as a life-threatening multi-organ dysfunction triggered by an uncontrolled host response to infectious disease. Systemic inflammation elicited by sepsis can cause acute cerebral dysfunction, characterized by delirium, coma, and cognitive dysfunction, known as septic encephalopathy. Recent evidence has reported the underlying mechanisms of sepsis. However, the reasons for the development of inflammation and degeneration in some brain regions and the persistence of neuroinflammation remain unclear. This mini-review describes the pathophysiology of region-specific inflammation after sepsis-associated encephalopathy (SAE), clinical features, and future prospects for SAE treatment. The hippocampus is highly susceptible to inflammation, and studies that perform treatments with antibodies to cytokine receptors, such as interleukin-1β, are in progress. Future development of clinically applicable therapies is expected.